2005
DOI: 10.1111/j.0105-1873.2005.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and patch test study of patients with positive patch test reactions to fragrance mix in China

Abstract: The clinical and patch test (PT) features of patients with positive PT reactions to fragrance mix (FM) were studied. 378 consecutive eczema outpatients patch tested with a modified European standard series were analysed. 60 patients (15.9%) reacted to FM. No significant differences could be found between the ages of FM PT-positive and PT-negative patients [median age 40.5 (range from 18 years to 69 years) versus median age 37.5 (range from 5 years to 81 years), rank sum test, P = 0.301]. FM PT-positive rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Concomitant reactions to colophonium are often seen in patients reacting to fragrance markers (9, 19–25). In this study, as in earlier studies on ox.…”
supporting
confidence: 61%
“…Concomitant reactions to colophonium are often seen in patients reacting to fragrance markers (9, 19–25). In this study, as in earlier studies on ox.…”
supporting
confidence: 61%
“…In the recent study by Mann et al (2), only 57.6% of patients tested with an extended series of fragrance ingredients (the 26 substances required to be labelled in the EU) also reacted to a fragrance marker in the baseline series. In 2005, we reported that the prevalence of contact allergy to FM I in patients with eczema was 15.9% (3). Given that more and more Chinese are using fragrance-containing cosmetics, and are also exposed to traditional Chinese medicine (TCM), which may also contain fragrances, it is interesting to study fragrance allergy beyond FM I in China.…”
mentioning
confidence: 99%
“…In this patient, lesions appeared 1 day after taking traditional Chinese medicine Xi‐Huang capsule. According to Li Lin‐Feng et al, TCM was the common cause of fragrance allergy 17,18 . According to the medication taking history, we suspected that the fragrance in the Xi‐Huang capsule was the cause of the lesions.…”
Section: Discussionmentioning
confidence: 97%
“…TCM was the common cause of fragrance allergy. 17,18 According to the medication taking history, we suspected that the fragrance in the Xi-Huang capsule was the cause of the lesions. But the results of patch test with colophony, fragrance mix, balsam of peru are all negative and the patch tests with Xi-Huang capsule (5% and 10% in petroleum) were positive.…”
Section: Discussionmentioning
confidence: 99%